Cost-effective solar cookers: A global review. (1st September 2020) - Arunachala, U.C.; Kundapur, Ashok
Highlights: Plenty of box and parabolic cooker designs have been discussed. Low-cost cookers like Panel and Funnel, Fresnel designs have been dealt in detail. The role of solar cookers at the domestic, community, and commercial level is highlighted. Abstract: One of the primary factors affecting the amount of global energy consumption and related greenhouse gas emissions is cooking. Solar cooking is an appropriate solution because it is inexpensive and expandable. To unfurl the cost-effective solar cooker designs, this paper presents a review of such cookers viz. Box cooker with or without reflectors, Panels, and Funnels. Other designs representing practically all categories of solar cookers, like Parabolic-dish and trough type, Fresnel, and indirect type are also mentioned. Further discussion includes scope for design improvement, economical aspects, performance evaluation criteria, and heat conservation concepts. The necessity of round the clock, high temperature based indoor solar cooking system is also emphasized.